Design and production of educational video games for the inclusion of deaf children (2022)
This work presents the design and development of an educational video game, a product committed to the project "Model for the production of educational digital content for the inclusion of deaf people" attached to the national program financed by Colciencias - Colombia: "Educational and technological pedagogical architecture for teacher training in and for diversity". The video game was made under the logic of applied and design research. It recognizes the importance of this resource as a didactic tool, which enhances and strengthens the learning process in deaf and hearing children, in the area of natural sciences. Instructional design includes: topic, purpose, target audience, learning objectives, and competencies. For its planning, elaboration and development, the environment, the rules, the challenge and the genre of the game were taken into account, deriving the prototype in the Unity engine